(untitled) (AmeriQuests, 2022)
This opinion piece argues the power and potential of the sister city relationship in promoting sustainable citizen diplomacy. This piece highlights the initiation of two sister city relationships by Senator Bernie Sanders, in his missions to set national precedence during heightened political conflict during the Cold War.